Understanding the use of film therapy as stress relief towards viewer’s emotional effect / Rahimah Abdul Rahim …[et al.] - Abdul Rahim, Rahimah; Mat Noordin, Noor Nirwandy; Jaafar, Siti Atikah (Faculty of Communication and Media Studies (FCMS), 2023)
The field of media communication is one of the broader fields due to the range of things that can be found within it. The movie industry is one of the sectors that is closely tied to and also derives from the media communication branch. Many groups around the world, including the Malaysian community, love watching movies and dramas at home or in the theatre as a way to decompress. This is due to the fact that viewing dramas and movies has evolved into a stress-relieving hobby. With adults being the only exception, movies are the most generally accessible and simply understood kind of entertainment in cinema, and they have a significant impact on audience behaviour, especially that of teenagers and young children. The film also has elements that may affect a viewer's psychology in addition to their emotional responses to it. Psychology is one of the only subjects that requires us to observe and participate in a variety of actions and illusions in order to learn. However, how the material is presented inside the movie itself also plays a part in this. The aim of this study is to understand the idea of therapeutic films and how effective they are in reducing viewers' stress in Malaysia. This study also determined whether or not using movie therapy may help people better manage their stress. The qualitative method of conducting in-depth interviews was used to collect information for this study. Five subject matter expert individuals in the field of film participated in interviews. These interviews served the objective of gathering their opinions on the emotional impact that dramas and films had on viewers. The findings from the interviews conclude that the utilization of therapeutic films to assist in lowering levels of stress among audiences in Malaysia is successful.